Cardiovascular manifestations of Lyme disease - a literature review - Lubaszka, Zuzanna; Fiega, Jakub; Michalska, Milena; Żurek, Urszula; Szewczyk, Dorota; Sikorska, Ewa (Journal of Education, Health and Sport, 2023)
Lyme disease is an infectious zoonosis transmitted by ticks infected with Borrelia spirochetes. Condition affects multiple organ systems and typically has a protracted course. Although Lyme carditis is a comparatively rare symptom of Lyme borreliosis, it can cause major cardiac conditions, including death, if left untreated. Atrioventricular block of various degrees is the hallmark of cardiac involvement, although other manifestations of the disease are increasingly describe such as ventricular and supraventricular arrhythmias, pericarditis, acute coronary syndrome, mild heart failure, cardiac tamponade or individual cases of cardiomyopathy, degenerative valvular lesions and vasculitis. Cardiovascular conduction disorders have a good prognosis despite their abrupt onset and completely resolve after a few days of antibiotic therapy. Therefore, a wait-and-see attitude should be maintained. However, a temporary or permanent pacemaker may be required if the patient’s clinical condition necessitates prompt intervention. Nevertheless, current recommendations suggest avoiding temporary stimulation wherever possible and limiting its use to the shortest treatment time possible.